2012
DOI: 10.3126/kumj.v9i2.6287
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sexually Transmitted Infections in a Tertiary Care Centre

Abstract: Background The burden of sexually transmitted infections is huge and is disproportionately affecting developing nations. In Nepal, recent available data on sexually transmitted infections are mostly targeted to high risk population. A prevalence study was thus done to explore the pattern of sexually transmitted infection syndromes among general population of Nepal. Objectives To highlight the prevalence and changing pattern of sexually transmitted infections among general population. Methods A retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
3
8
1
Order By: Relevance
“…In this study, the average age of the patients was 30.84 years with male to female ratio of 2.03:1. Similar pattern of male preponderance was reported in other studies too 4,5 . The reason for lesser number of female patients may be due to less pronounced symptoms in females compared to males and also due to reluctance among females to share their problems.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the average age of the patients was 30.84 years with male to female ratio of 2.03:1. Similar pattern of male preponderance was reported in other studies too 4,5 . The reason for lesser number of female patients may be due to less pronounced symptoms in females compared to males and also due to reluctance among females to share their problems.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study the prevalence of sexually transmitted infections was 6.2% which is lower than that reported in few studies [8,9], and higher than that reported by other investigators [10,11] indicating differences in methodology, study population and time of the study.…”
Section: Discussioncontrasting
confidence: 82%
“…Currently, over 60,000 people are estimated to be infected and common among sexually active age group particularly among male migrant workers. Overall HIV prevalence in Nepal is estimated at 0.30% in the adult population and it is categorized as a concentrated epidemic [54]. The TB-HIV co-infection rate (the prevalence of HIV infection among TB patients) in Nepal is 2.4% [55].…”
Section: Helicobacter Pylori Infectionmentioning
confidence: 99%
“…Of the patients studied, only 7.7% used condoms consistently [53]. One study showed high STI prevalence among drivers/conductors and migrant workers of sexually active age group [54]. Hence, STI is more common in Districts with highways running through.…”
Section: Helicobacter Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation